Distribution snd Ecology of the Malaysian Mahseer (Genus: Tor) in Kenyir Lake, Malaysia - Sopha, Lieng (1999)
A study on distribution and ecology of the Malaysian mahseer ( Tor sora Cuvier & Valenciennes and Tor tambroides Bleeker) was carried out in lotic and lentic habitats in Lake Kenyir, Malaysia. The fish distribution and habitat profile of the Malaysian mahseer were studied to investigate the ecological condition and their relationship with the environment and to determine the present spatial distribution and abundance in the lake system. The results showed that there is a habitat selection by fish of different sizes, (fingerling 2.0 - 7.0 cm, juveniles 7.1 - 20.0 cm and adults >20.0 cm TL) in relation with size of stream, water depth, current velocity, substrate, water temperature, water transparency, dissolved oxygen, and habitat types. The adults of Tor tambroides were most abundant in deeper parts or pools in upstream reaches of large streams (26-60 m width) of Sg. Tembat and Sg. Terengganu and medium-sized stream ( 1 2-25 m width) of Sungai Kiang. The juvenile were found in all sizes of sampled streams in the lake. The adult of T. sora were found in less abundance in small and medium-sized streams of Sg. Buluh Nipis n, Sg. Mandak I and n, Sg. Siput, and Sg. Lancang. However, the juveniles and fingerlings were mostly found in the small stream reaches and were most abundant at water depths ranging from 10 to 187 cm with velocity ranging from 1 to 118 cm.s·l. The adults occurred in habitats where the water depth was about 5.4 m and current velocity ranged from 1 to 66 cm.s·l. The fingerling and juvenile of both species were frequently found in streams where pools represented from 3 to 9%, runs 5 to 32%, riffles 61 to 91 % of the total area. The fingerlings and juveniles were mostly found in habitats where boulders were predominant followed by bedrock, sand, gravel, cobble and pebble. The adults mostly occurred in habitats where the substrate comprised of boulders and rock. The young mahseers were frequently found in clear-running water, while the adults occurred in slow-running and more turbid water as compared to the young mahseer. The temperature profile ranged from 23.0 to 2S.3°C. the dissolved oxygen varied from 6.7 to 8.8 mg.rl. The water hardness of the mahseer habitat nullifies the effect of toxic metals to the fish. The microhabitat and macrohabitat analysis of habitat use and preference of T. soro in the two small stream reaches of Sg. Buluh Nipis IT and Sg. Mandak IT showed that T. soro preferred depths between 52 em and 120 em and water velocity between 0 and 35 cm.s·l. Different size classes of T. sora used different mean depths at both sites. The seasonal use of depth and velocity by T. sora were significantly different at both sites (p<O.OS). T. sora preferred sand and gravel as substrate. T. sora preferred cover up to 70% and the fish of all size had similar preference for cover at both sites (p>O.OS). T. sora generally aggregated in groups ranging from 1 to 7 fish and were fou nd to associate with Acrossocheilus dearatus (C & V) and Osteochilus vittatus (C & V). The adults of T. sora were fou nd in pools. The juveniles were quite well spread in all habitat types, pools, runs and ri ffles, while the fingerl ings were most abundant in riffle habitat. It was found that T. soro fed mainly on algae and other available fauna and flora at the stream of Sg. Buluh Nipis II. Examining their feeding apparatus, the teeth of T. sora (7.0 -26.0 cm in TL) and T. tambroides (17.0 - 25.0 cm in TL) were not developed on the lower and upper jaw, but there is a presence of pharyngeal te€th on the upper and lower pharyngeal arch. Their mouths were protracted and slightly inferior. The lips of both fish species were thick. Being a typical cyprinid, both fish species had no conventional stomach and possessed an extended long intestine. The fish employed suction feeding in adaptation with their feeding apparatus. The relative length of gut (R.L.G.) for the T. sora with the size range from 7.0 to 26.0 cm in total length has been found to vary from the lowest 0.77 to the highest 2.85. The value of R.L.G. for T. tambraides with size ranging from 17.0 to 25.0 cm in total length also varies, ranging from l.11 to 2.50. Both fish species were omnivores as evident from gut content analysis and the relative length of gut. It could be concluded that the mahseer is a highly territorial fish species. The physical and chemical parameters are significant in determining spatial distribution and abundance of the Malaysian mahseer and also important in the application of habitat-based management of the mahseer population in Lake Kenyir.